IN SILICO ANALYSIS PREDICTS AN AMINO ACID PERMEASE FAMILY PROTEIN AS THE PUTATIVE CANDIDATE GENE UNDERLYING A MAJOR QTL FOR TILLER NUMBER IN RICE (Oryza sativa L.) - KEERTHI ISSA, LAKSHMINARAYANA R. VEMIREDDY, ESWARAYYA RAMI REDDY, LAL AHAMED MOHAMMAD AND P. LAVANYA KUMARI, (The Journal of Research ANGRAU, 2022)
Rice (Oryza sativa L.) yield and it’s component traits are known to have complex inheritanceand are controlled by several genes with small effects. Although several genomic regions or quantitativetrait loci (QTLs) are identified for a galaxy of traits in rice, only a few candidate genes underlyingthese QTLs have been functionally characterized as involvement of the laborious and time-consumingfine mapping and map-based cloning strategies. However, with the advances in sequencingtechnologies, now a wealth of information related to genomics, transcriptomics, proteomics andmetabolomics has been publicly available. Exploiting these databases, in the present investigation,we predicted amino acid permease (AAP) (LOC_Os01g71720), as a candidate gene underlying amajor effective QTL for tiller number. The candidature of the OsAAP for tiller number QTL has beenendorsed by the literature mining, QTG finder, GO analysis, sequence variation, and gene expressionanalysis. Therefore, this OsAAP could be targeted for further functional analysis before being exploitedin future rice breeding.